2017
DOI: 10.1160/th16-10-0814
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies for atherosclerosis and atherothrombosis: Past, present and future

Abstract: SummaryEven two centuries after they were first described, atherosclerosis and atherothrombosis remain among the leading causes of death worldwide. Over the last decades it has become clear that atherosclerosis is not only a lipid-driven disease but also a multifactorial process largely driven by inflammatory mediators, an insight that has instigated additional research and drug development focussing on anti-inflammatory therapies. In this review, we will provide a brief historical overview, followed by a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 82 publications
(85 reference statements)
0
35
0
1
Order By: Relevance
“…24 Integrating gender specificities in scientific statements, medical investigations, and practical guidelines will be determinant in improving women's health care. 25,26…”
Section: Resultsmentioning
confidence: 99%
“…24 Integrating gender specificities in scientific statements, medical investigations, and practical guidelines will be determinant in improving women's health care. 25,26…”
Section: Resultsmentioning
confidence: 99%
“…In acute coronary syndrome (ACS) patients oxLDL binding to platelets correlates with activation status . Intraplatelet oxLDL levels are elevated in coronary artery disease (CAD) patients, particularly in ACS patients diagnosed with intracoronary thrombi, suggesting that platelet‐lipid associations may enhance thrombotic risk …”
Section: Platelets and Lipids: Age‐old Accomplicesmentioning
confidence: 99%
“…Most likely, new cholesterol lowering drugs would also initially be used for individuals with these severe diseases as well. Finally, these drugs are cost prohibitive and may increase health care costs by 38% over the next 5 years [135, 146]. …”
Section: 0 Existing and Potential Therapeutic Targetsmentioning
confidence: 99%
“…Prior to its approval in 2013, phase 3 clinical trials indicated a reduction in LDL-associated circulating cholesterol by 25–40% [152, 153]. However, Mipomersen is similarly only approved for those suffering from homozygous familial hypercholesteremia and has not been approved for use in Europe due to concerns with liver toxicity and other side effects [135, 137, 148, 154]. Further investigation is undoubtedly required to understand the long-term effects of this drug in humans.…”
Section: 0 Existing and Potential Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation